Microbial Control of White Grubs in Nepal: The Way Forward - GC, Yubak Dhoj (Journal of Agriculture and Environment, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Nepalese economy is largely dependent on agriculture. Over the time, there has been gradual transformation in the agricultural production system and the hitherto dominant chemical based agricultural system has been gradually changing with the latest aspects of bio-rational approaches. Emphasis towards these aspects has been seen both in the governmental and non-governmental level through their commitments in long term prospective plans. However, there is long way to go towards bio-rational approach of pest control in Nepal. This aspect is newer concept in case of Nepal. Institute of Agriculture and Animal Science (IAAS), Department of Entomology, Rampur, in support of Helvetas had initiated bio-pesticides production. The major effort was the production and use of biopesticide based on fungal pathogen (Metarhizium anisopliae Sorokin) against white grubs in particular and soil insect in general. The research was carried out for about a decade and results so far indicated the ample scope of producing and using this agent against this dreaded pest. The research results so far obtained are at get set position, however, to gear up the further works, it has been felt that joint efforts from possible counterparts such as Nepal Agricultural Research Council (NARC), IAAS, Department Of Agriculture (DOA), private organisations, NGOs and INGOs would be vital. It has been realised to form national working groups for the development of microbial pest control. Major lead should be taken by national organisations in full support of private organisations. This paper has been brought forth in order to bring into the information of the works so far done in Nepal and to arouse the interest among the possible counterparts, producers, consumers, planners, and policy makers. Key words: Bio-rational compounds; Bio-pesticides; IPM; Metarhizium anisopliae; White grubs The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 156-165